1986
DOI: 10.1021/jm00161a028
|View full text |Cite
|
Sign up to set email alerts
|

Azasteroids: structure-activity relationships for inhibition of 5.alpha.-reductase and of androgen receptor binding

Abstract: A series of steroids, primarily 4-azasteroids, were prepared and tested in vitro as inhibitors of human and rat prostatic 5 alpha-reductase and of binding of dihydrotestosterone to the rat androgen receptor. The primary structural modifications were changes of the A ring and of moieties attached at the C-17 position of the steroid nucleus. New A-ring modifications included the 4-cyano-3-oxo-delta 4 system in the carbocyclic series and 1 alpha-CN, 1 alpha-CH3, 1 alpha,2 alpha-CH2, 2 beta-F, 2-aza, 2-oxa, and A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(85 citation statements)
references
References 5 publications
2
82
0
1
Order By: Relevance
“…21 The IC50 value of finasteride to rat 5α-SR in prostate microsomes was also evaluated to be 11 nM by Häusler et al, 22 13 nM by Igarashi et al 23 and 237 nM by Mitamura et al 13 The reported IC50 values of fenasteride to rat 5α-SR in prostate homogenate were in the range from 6.8 to 147 nM. [24][25][26][27][28][29][30] The reason for such a difference may be related to differences in experimental conditions of enzyme activity evaluation such as pH, testosterone concentration and enzyme preparation.…”
Section: Assays Of Inhibitory Activity Of Finasteridementioning
confidence: 99%
“…21 The IC50 value of finasteride to rat 5α-SR in prostate microsomes was also evaluated to be 11 nM by Häusler et al, 22 13 nM by Igarashi et al 23 and 237 nM by Mitamura et al 13 The reported IC50 values of fenasteride to rat 5α-SR in prostate homogenate were in the range from 6.8 to 147 nM. [24][25][26][27][28][29][30] The reason for such a difference may be related to differences in experimental conditions of enzyme activity evaluation such as pH, testosterone concentration and enzyme preparation.…”
Section: Assays Of Inhibitory Activity Of Finasteridementioning
confidence: 99%
“…Finasteride [17β-(N-tert-butylcarbamoyl)-4-aza-5α-androst-1-en-3-one] (1) is a potent inhibitor of 5α-reductase, an enzyme which catalyzes the conversion of testosterone into dihydrotestosterone in many organs [1]. Finasteride (1) is used in the treatment of hair loss [2], and benign prostate hyperplasia, both these disorders are associated with in-situ high levels of increased dihydrotestosterone.…”
Section: Introductionmentioning
confidence: 99%
“…It is also employed for the prevention of prostate cancer [3]. Previously, biotransformation of finasteride (1) has been reported by various fungi, including Selenastrum capricornutum [4], Mortierella isabellina, Cunninghamella elegans, and Bacillus megaterium [5].…”
Section: Introductionmentioning
confidence: 99%
“…Dutasteride belongs to azasteriod class of compounds and function as a 5α-reductase inhibitor 1 which prevents the conversion of the androgen sex hormone testosterone into the more potent metabolite dihydrotestosterone (DHT). In 2009, South Korea has been licensed dutasteride for the treatment of androgenetic alopecia and in Japan 2015.…”
Section: Introductionmentioning
confidence: 99%